Tricuspid atresia with absent pulmonary valve: A rare form of single ventricle. Issue 7 (17th April 2022) - Naik, Ronak; Makadia, Luv D.; Ramirez, Michelle; Crawford, Maya T.; Ahmad, Latifah; Kumar, T. K. Susheel
Abstract: Tricuspid atresia with an absent pulmonary valve is a rare congenital cardiac defect. Although extensive pathological reviews have been published in the past, there are only a handful of cases that have been successfully palliated to the stage of Fontan. We hereby describe the successful management of one such case and review the surgical strategies described in the literature.